Heterotopic bone formation in the musculus latissimus dorsi of sheep using β-tricalcium phosphate scaffolds: evaluation of different seeding techniques. Issue 2 (27th November 2017) - Spalthoff, Simon; Zimmerer, Rüdiger; Dittmann, Jan; Kokemüller, Horst; Tiede, Marco; Flohr, Laura; Korn, Philippe; Gellrich, Nils-Claudius; Jehn, Philipp
Abstract: Osseous reconstruction of large bone defects remains a challenge in oral and maxillofacial surgery. In addition to autogenous bone grafts, which despite potential donor-site mobility still represent the gold standard in reconstructive surgery, many studies have investigated less invasive alternatives such as in vitro cultivation techniques. This study compared different types of seeding techniques on pure β-tricalcium phosphate scaffolds in terms of bone formation and ceramic resorption in vivo . Cylindrical scaffolds loaded with autologous cancellous bone, venous blood, bone marrow aspirate concentrate or extracorporeal in vitro cultivated bone marrow stromal cells were cultured in sheep on a perforator vessel of the musculus latissimus dorsi over a 6-month period. Histological and histomorphometric analyses revealed that scaffolds loaded with cancellous bone were superior at promoting heterotopic bone formation and ceramic degradation, with autogenous bone and bone marrow aspirate concentrate inducing in vivo formation of vital bone tissue. These results confirm that autologous bone constitutes the preferred source of osteoinductive and osteogenic material that can reliably induce heterotopic bone formation in vivo .